Nanocellulose graphene quantum dot high-sensitivity humidity sensor and its green preparation process
Through the combination of porous composite moisture membrane and flexible electrode combination of nano cellulose, graphene quantum dot, and polymailing silicone, solve the lack of existing humidity sensors in attachment and response sensitivity, realizing high sensitivity and high sensitivity and achievement Long -term stability humidity sensor is suitable for a variety of application areas.
Patent Information
- Application Number
- CN202010967599.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-09-15
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2040-09-15
AI Technical Summary
The existing humidity sensors have shortcomings in the adhesion and response sensitivity of the moisture-sensitive film, and the preparation process is complex, which affects the stability of long-term use.
Using nano -cellulose, graphene quantum dot, and polymethyl siliconxane mixing porous composite wet -sensitive membranes by proportion, combined with flexible electrodes and wires, build a three -dimensional porous network structure through vacuum frozen drying technology to improve the sensitivity and stability of the sensor sex.
The high sensitivity, rapid response/recovery behavior, and good long -term use stability are realized, and environmentally friendly materials, green preparation processes are suitable for industrial intelligent production and wearable equipment.
Smart Images

Figure CN112067670B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomass nanomaterials, and more specifically, to a nanocellulose graphene quantum dot high-sensitivity humidity sensor with high sensitivity, flexibility, three-dimensional porosity, sensitive sensing and high humidity detection accuracy, and a green preparation process thereof. Background Art
[0002] In the fields of industrial intelligent production, storage and transportation of hazardous goods, agricultural and forestry breeding, wearable smart electronic devices, meteorological remote sensing testing, cultural relics protection, health monitoring, etc., the humidity sensors used are required to have higher accuracy and sensitivity, faster response / recovery behavior and good long-term stability.
[0003] Nanocellulose has good stability, biocompatibility, flexibility and excellent self-assembly performance. There are a large number of oxygen-containing groups on the surface of its molecular chain, showing high hydrophilicity, and is an ideal humidity-sensitive material. In the existing reported technology, nanocellulose and graphene oxide composite materials are used to prepare humidity sensors. The humidity test range can reach 25-85% RH. Its relative capacitance shows a certain change trend with humidity changes, and the humidity change trend measured by commercial hygrometers is not much different during humidity tests, but the hygroscopicity is large and the response time is long. Graphene quantum dots, as graphene derivatives, also have abundant oxygen-containing groups and large surface areas on the surface, and have been used to prepare new sensing materials. Existing related studies have proposed the use of spin coating to prepare graphene oxide quantum dot humidity sensors, which can achieve sub-second response, but the adhesion of the humidity-sensitive film is not high and is easily disturbed by external environmental factors, thereby affecting the response sensitivity of the humidity sensor. In addition, there are also studies using interdigital electrodes to assemble humidity sensors, but due to the cumbersome preparation process and the metal film on the electrode is easily oxidized, thereby weakening its conductive properties, thereby affecting the long-term test stability. Therefore, it is necessary to further optimize the structure and properties of humidity-sensitive materials, develop new flexible electrode materials, promote their application in flexible wearable devices, etc., and broaden the application fields of biomass nanomaterials. Summary of the invention
[0004] An object of the present invention is to address at least the above-mentioned disadvantages and to provide at least the advantages which will be described hereinafter.
[0005] Another object of the present invention is to provide a nanocellulose graphene quantum dot humidity sensor with high sensitivity, excellent sensing performance and stable performance.
[0006] In order to achieve these purposes and other advantages of the present invention, the present invention provides a nanocellulose graphene quantum dot high-sensitivity humidity sensor, comprising:
[0007] A porous composite humidity-sensitive membrane is prepared by mixing nanocellulose, graphene quantum dots and polydimethylsiloxane in a certain proportion, wherein the porous composite humidity-sensitive membrane constitutes a sensing surface;
[0008] A polydimethylsiloxane layer coated on the side of the porous composite moisture-sensitive membrane;
[0009] a flexible electrode adhered to the side of the porous composite moisture-sensitive membrane through a polydimethylsiloxane layer;
[0010] Wires connected to the flexible electrodes.
[0011] In the above scheme, the sensing medium layer of the humidity sensor is a porous composite humidity-sensitive membrane prepared by nanocellulose, graphene quantum dots and polydimethylsiloxane. Nanocellulose and graphene quantum dots are interlaced and combined with each other to form a flexible three-dimensional porous network structure with a large specific surface area. Polydimethylsiloxane improves the stability of the porous network structure, thereby effectively promoting the conduction and penetration of water molecules on the pore surface of the composite humidity-sensitive membrane, thereby improving the sensitivity and sensing performance of the sensor.
[0012] Preferably, in the nanocellulose graphene quantum dot high-sensitivity humidity sensor, the nanocellulose is one or more of nanofibrillar cellulose, cellulose nanocrystals and bacterial cellulose;
[0013] The graphene quantum dots are one or more of graphene quantum dots and graphene oxide quantum dots.
[0014] Preferably, in the nanocellulose graphene quantum dot high-sensitivity humidity sensor, the flexible electrode is a nanocellulose carbon nanotube composite film with a thickness of 0.01 to 0.1 mm and a square resistance of 20 to 390 Ω / □.
[0015] Preferably, in the nanocellulose graphene quantum dot high-sensitivity humidity sensor, the anti-interference shielding wire is connected to the flexible electrode through conductive silver glue.
[0016] Preferably, the nanocellulose graphene quantum dot high-sensitivity humidity sensor further comprises:
[0017] A rubber belt, with fasteners at both ends thereof so as to be fastened into a loop or to other devices, a plurality of grooves are arranged along the belt surface of the rubber belt, the grooves may or may not pass through the rubber belt, the shape of the grooves matches the shape of the porous composite humidity-sensitive membrane so that the porous composite humidity-sensitive membrane is embedded in the grooves, and the side walls of the grooves are also provided with recessed grooves so as to accommodate the flexible electrodes, a wire track is arranged on either side of the groove, the wire track extends straightly inside the rubber belt along the length direction of the rubber belt, and the wire passes through the recessed groove into the wire track and is arranged along the wire track;
[0018] A central processing module, which is buried inside the rubber belt and close to the two ends of the rubber belt, the central processing module includes a processing unit and a storage unit, and the wire extends and is connected to the processing unit;
[0019] The wiring terminals are arranged at both ends of the rubber belt for connecting with other devices, and the wiring terminals are connected to the central processing module.
[0020] In the above solution, multiple sensors are integrated on a rubber belt. The rubber belt can be used as a separate wearable device or in conjunction with other devices such as a watch. It is simple and fast and can effectively solve the practical application problems of sensors.
[0021] At the same time, the grooves on the rubber belt match the humidity-sensitive film, and the conductive electrodes are contained in the recessed grooves, which reduces contact with the outside world and avoids damage, thereby improving the stability of the sensing performance.
[0022] In addition, the line transmits the signals of multiple humidity-sensitive films to the central processing module, which is convenient for the central processing module to collect and store the signals of multiple humidity-sensitive films to obtain more accurate humidity information.
[0023] A green preparation process for a nanocellulose graphene quantum dot high-sensitivity humidity sensor comprises the following steps:
[0024] Step 1: After mixing nanocellulose and graphene quantum dots in a certain proportion, ultrasonically disperse the mixture to obtain a dispersion; uniformly mix polydimethylsiloxane with the obtained dispersion to obtain a mixed dispersion; and vacuum freeze-dry the obtained mixed dispersion to prepare a porous composite humidity-sensitive membrane;
[0025] Step 2: evenly coating polydimethylsiloxane on the left and right sides of the porous composite humidity-sensitive membrane, wherein the upper and lower sides of the porous composite humidity-sensitive membrane form sensing surfaces;
[0026] Step 3, pasting the nanocellulose carbon nanotube composite film to the left and right sides of the porous composite humidity sensitive film to form a flexible electrode;
[0027] Step 4: Connect the wire used to connect to the external device to the flexible electrode to obtain the nanocellulose graphene quantum dot high-sensitivity humidity sensor.
[0028] In the above technical solution, the preparation process adopts an ultrasonic dispersion process to enhance the uniformity of the mixed dispersion, and promotes the formation of a three-dimensional porous network structure of the composite humidity-sensitive membrane through vacuum freeze-drying technology.
[0029] Preferably, the green preparation process of the nanocellulose graphene quantum dot high-sensitivity humidity sensor specifically includes:
[0030] Step A, preparing a nanocellulose dispersion with a concentration of 1 to 50 mg / ml and a graphene quantum dot dispersion with a concentration of 1 to 20 mg / ml;
[0031] Step B, subjecting the nanocellulose dispersion and the graphene quantum dot dispersion to high-efficiency ultrasonic dispersion for 5 to 60 minutes respectively to obtain uniform nanocellulose dispersion and graphene quantum dot dispersion;
[0032] Step C, mixing a uniform nanocellulose dispersion and a graphene quantum dot dispersion in a certain proportion, and ultrasonically dispersing for 20 to 120 minutes at an ultrasonic power of 400 to 1200 W to obtain a uniformly dispersed nanocellulose graphene quantum dot dispersion; wherein the graphene quantum dots account for 0.5 to 100 wt.% of the total dry weight of the nanocellulose and the graphene quantum dots;
[0033] Step D, adding a certain amount of polydimethylsiloxane to the nanocellulose graphene quantum dot dispersion, and obtaining a mixed dispersion after magnetic stirring and ultrasonic dispersion; wherein the polydimethylsiloxane accounts for 10 to 50 wt.% of the total dry weight of the nanocellulose, graphene quantum dots and polydimethylsiloxane;
[0034] Step E, placing the obtained mixed dispersion into a vacuum freeze dryer, controlling the temperature to -50°C, freezing for 2 to 6 hours, then taking it out and placing it on a sample rack, vacuum drying for 24 to 72 hours to obtain a porous composite humidity-sensitive membrane; the porous composite humidity-sensitive membrane has a thickness of 0.5 to 20 mm;
[0035] Step F, mixing the nanocellulose dispersion and the carbon nanotubes, and preparing a nanocellulose carbon nanotube composite film by ultrasonic dispersion, suction filtration, and drying; the nanocellulose carbon nanotube composite film has a thickness of 0.01 to 0.1 mm and a square resistance of 20 to 390 Ω / □;
[0036] Step G, coating polydimethylsiloxane on the side of the porous composite humidity-sensitive membrane, pasting the nanocellulose carbon nanotube composite membrane cut according to predetermined specifications on the side of the porous composite humidity-sensitive membrane, and then curing at 85° C. for 6 to 12 hours to obtain an assembled sensor;
[0037] Step H: lay the assembled sensor flat, evenly apply conductive silver glue on both sides of the nanocellulose carbon nanotube composite film, connect it with the wire, and ensure good contact with external equipment.
[0038] The present invention has at least the following beneficial effects:
[0039] First, the nanocellulose graphene quantum dot high-sensitivity humidity sensor proposed in the present invention is prepared with a certain ratio of nanocellulose and graphene quantum dot composite film as humidity-sensitive materials. The nanocellulose with a high aspect ratio and the graphene quantum dots with a large specific surface area can effectively construct a good three-dimensional porous network structure through vacuum freeze drying, which is conducive to its contact with water molecules in the external environment, increases the water molecule transmission channel, promotes water molecule conduction, and then allows water molecules to quickly penetrate the network structure. Therefore, the humidity sensor can obtain a high sensitivity value and achieve a fast response / recovery behavior.
[0040] Secondly, the electrode used in the present invention is a highly conductive nanocellulose carbon nanotube composite film, which has good flexibility and can better conduct the sensing signal of the sensor, thereby improving the response characteristics of the sensor.
[0041] Furthermore, the nanocellulose and graphene quantum dots used in the present invention are both environmentally friendly and green materials. No toxic and odorous volatile substances are generated during the mixing and preparation process, so the prepared nanocellulose graphene quantum dot high-sensitivity humidity sensor has green and environmentally friendly performance.
[0042] In addition, the present invention uses nanocellulose with good self-assembly performance and enhanced performance, so that the prepared nanocellulose graphene quantum dot high-sensitivity humidity sensor has high flexibility and excellent bending resistance, making it easy to assemble into devices, and can promote its application development in wearable devices and other fields.
[0043] In addition, the polydimethylsiloxane used in the present invention can serve as a bridge connecting nanocellulose and graphene quantum dots, making the three-dimensional porous network structure of the porous composite humidity sensitive membrane more stable, while improving the adhesion of the porous composite humidity sensitive membrane to the electrode, and effectively improving the long-term use stability of the porous composite humidity sensitive membrane; in the assembly process of the humidity sensor, polydimethylsiloxane also exhibits a good encapsulation effect.
[0044] In addition, the present invention integrates multiple sensors on a rubber belt. The rubber belt can be used as a separate wearable device or in conjunction with other devices such as a watch or a mobile phone. It is simple and fast and can effectively solve the practical application problems of the sensors.
[0045] At the same time, the grooves on the rubber belt match the humidity-sensitive film, and the conductive electrodes are contained in the recessed grooves, which reduces contact with the outside world and avoids damage, thereby improving the stability of the sensing performance.
[0046] In addition, the line transmits the signals of multiple humidity-sensitive films to the central processing module, which is convenient for the central processing module to collect and store the signals of multiple humidity-sensitive films to obtain more accurate humidity information.
[0047] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a schematic structural diagram of the first embodiment of the nanocellulose graphene quantum dot high-sensitivity humidity sensor of the present invention;
[0049] Figure 2 This is a schematic structural diagram of a second embodiment of the nanocellulose graphene quantum dot high-sensitivity humidity sensor of the present invention;
[0050] Figure 3 for Figure 2 Sectional view in the AA direction;
[0051] Figure 4 This is a scanning electron microscope image of the porous humidity-sensitive membrane prepared in Example 3;
[0052] Figure 5 This is a scanning electron microscope image of the humidity sensitive film prepared in Comparative Example 1;
[0053] Figure 6 The humidity sensitivity curve diagram of the nanocellulose graphene quantum dot humidity sensor in implementation 3;
[0054] Figure 7 This is a response / recovery time curve of the nanocellulose graphene quantum dot humidity sensor in Example 3;
[0055] Figure 8 This is a bending state diagram of the nanocellulose / graphene quantum dot / polydimethylsiloxane composite humidity-sensitive film in Example 3;
[0056] Fig. 9 This is a natural state diagram of the nanocellulose / graphene quantum dots / polydimethylsiloxane composite humidity-sensitive film in Example 3. DETAILED DESCRIPTION
[0057] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0058] like Figure 1 As shown, in the first embodiment, the structure of the nanocellulose graphene quantum dot high-sensitivity humidity sensor described in the present invention includes two flexible electrodes 1, a polydimethylsiloxane layer 2, and a porous composite humidity-sensitive membrane 3.
[0059] Among them, the sensing medium layer of the humidity sensor of the present invention is a porous composite humidity-sensitive membrane 3 prepared by nanocellulose, graphene quantum dots and polydimethylsiloxane. The nanocellulose and graphene quantum dots are interlaced and combined with each other to form a flexible three-dimensional porous network structure with a large specific surface area, and the addition of polydimethylsiloxane is beneficial to improving the stability of the porous network structure, thereby effectively promoting the conduction and penetration of water molecules on the surface of the composite membrane.
[0060] Further, if Figure 2 and 3 As shown, in the second embodiment, the nanocellulose graphene quantum dot high-sensitivity humidity sensor further includes:
[0061] A rubber belt 4 is provided with fasteners 9 at both ends so as to be fastened into a ring or to other devices such as a mobile phone or a watch body. A plurality of grooves 5 are provided along the belt surface of the rubber belt 4. The grooves 5 may or may not pass through the rubber belt. The shape of the grooves 5 matches the shape of the porous composite humidity-sensitive membrane 3 so that the porous composite humidity-sensitive membrane 3 is embedded in the grooves 5. Each groove 5 corresponds to a porous composite humidity-sensitive membrane 3 unit, and the side walls of the grooves 5 are also provided with recessed grooves 6 to accommodate the flexible electrode 1. A wire track 7 is provided on either side of the groove 5. The wire track 7 extends straight inside the rubber belt 4 along the length direction of the rubber belt 4, and the wire passes through the recessed groove 6 into the wire track 7 and is arranged along the wire track 7.
[0062] The central processing module 8 is buried inside the rubber belt 4 and close to the two ends of the rubber belt. The central processing module 8 includes a processing unit and a storage unit. The wire extends and is connected to the processing unit; the storage unit is connected to the processing unit to store information data.
[0063] The connection terminals 10 are arranged at both ends of the rubber belt 4 for connecting with other devices such as a watch body or a mobile phone, and the connection terminals are connected to the central processing module.
[0064] The main raw materials of nanocellulose graphene quantum dot high-sensitive humidity sensor are:
[0065] The nanocellulose is nanofibrillar fiber (NFC) or cellulose nanocrystal (CNC) or bacterial cellulose (BC); and the concentration of the dispersion liquid thereof is 1 to 50 mg / ml.
[0066] The graphene quantum dots are graphene quantum dots (GQDs) and graphene oxide quantum dots (GOQDs); the concentration of the dispersion liquid is 1 to 20 mg / ml.
[0067] The mass of polydimethylsiloxane (PDMS) is 4 to 20 mg, and the PDMS and the curing agent are mixed in a weight ratio of 10:1.
[0068] The electrode is a nanocellulose carbon nanotube composite film with a thickness of 0.01 to 0.1 mm.
[0069] Preparation method: preparation of nanocellulose / graphene quantum dots / polydimethylsiloxane composite humidity-sensitive film - preparation of nanocellulose carbon nanotube composite film - uniform coating of polydimethylsiloxane - assembly of electrodes - hot pressing and curing - connection of wires - pre-humidity test.
[0070] The prepared nanocellulose graphene quantum dot high-sensitivity humidity sensor has a humidity test range of 11-97% RH, a response sensitivity floating within the range of 1300-1350pF / % RH, a response / recovery time of 47-50s / 2-3s, and a long-term stable test deviation of ≤±3%.
[0071] Example 1
[0072] A green preparation process for a nanocellulose graphene quantum dot high-sensitivity humidity sensor comprises the following steps:
[0073] Step 1: After mixing nanocellulose and graphene quantum dots in a certain proportion, ultrasonically disperse the mixture to obtain a dispersion; uniformly mix polydimethylsiloxane with the obtained dispersion to obtain a mixed dispersion; and vacuum freeze-dry the obtained mixed dispersion to prepare a porous composite humidity-sensitive membrane;
[0074] Step 2: evenly coating polydimethylsiloxane on the left and right sides of the porous composite humidity-sensitive membrane, wherein the upper and lower sides of the porous composite humidity-sensitive membrane form sensing surfaces;
[0075] Step 3, pasting the nanocellulose carbon nanotube composite film to the left and right sides of the porous composite humidity sensitive film to form a flexible electrode;
[0076] Step 4: Connect the wire used to connect to the external device to the flexible electrode to obtain the nanocellulose graphene quantum dot high-sensitivity humidity sensor.
[0077] The prepared nanocellulose graphene quantum dot high-sensitivity humidity sensor has a humidity test range of 11-97% RH, a response sensitivity floating within the range of 1305pF / % RH, a response / recovery time of 50s / 3s, and a long-term stable test deviation of ≤±3%.
[0078] Example 2
[0079] The green preparation process of the nanocellulose graphene quantum dot high-sensitivity humidity sensor specifically includes:
[0080] Step A, preparing a nanocellulose dispersion with a concentration of 1 to 50 mg / ml and a graphene quantum dot dispersion with a concentration of 1 to 20 mg / ml;
[0081] Step B, subjecting the nanocellulose dispersion and the graphene quantum dot dispersion to high-efficiency ultrasonic dispersion for 5 to 60 minutes respectively to obtain uniform nanocellulose dispersion and graphene quantum dot dispersion;
[0082] Step C, mixing a uniform nanocellulose dispersion and a graphene quantum dot dispersion in a certain proportion, and ultrasonically dispersing for 20 to 120 minutes at an ultrasonic power of 400 to 1200 W to obtain a uniformly dispersed nanocellulose graphene quantum dot dispersion; wherein the graphene quantum dots account for 0.5 to 100 wt.% of the total dry weight of the nanocellulose and the graphene quantum dots;
[0083] Step D, adding a certain amount of polydimethylsiloxane to the nanocellulose graphene quantum dot dispersion, and obtaining a mixed dispersion after magnetic stirring and ultrasonic dispersion; wherein the polydimethylsiloxane accounts for 10 to 50 wt.% of the total dry weight of the nanocellulose, graphene quantum dots and polydimethylsiloxane;
[0084] Step E, placing the obtained mixed dispersion into a vacuum freeze dryer, controlling the temperature to -50°C, freezing for 2 to 6 hours, then taking it out and placing it on a sample rack, vacuum drying for 24 to 72 hours to obtain a porous composite humidity-sensitive membrane; the porous composite humidity-sensitive membrane has a thickness of 0.5 to 20 mm;
[0085] Step F, mixing the nanocellulose dispersion and the carbon nanotubes, and preparing a nanocellulose carbon nanotube composite film by ultrasonic dispersion, suction filtration, and drying; the nanocellulose carbon nanotube composite film has a thickness of 0.01 to 0.1 mm and a square resistance of 20 to 390 Ω / □;
[0086] Step G, coating polydimethylsiloxane on the side of the porous composite humidity-sensitive membrane, pasting the nanocellulose carbon nanotube composite membrane cut according to predetermined specifications on the side of the porous composite humidity-sensitive membrane, and then curing at 85° C. for 6 to 12 hours to obtain an assembled sensor;
[0087] Step H: lay the assembled sensor flat, evenly apply conductive silver glue on both sides of the nanocellulose carbon nanotube composite film and then connect it with the wire to ensure good contact with external equipment.
[0088] The prepared nanocellulose graphene quantum dot high-sensitivity humidity sensor has a humidity test range of 11-97% RH, a response sensitivity fluctuating around 1325pF / % RH, a response / recovery time of 47s / 2.5s, and a long-term stable test deviation of ≤±2%.
[0089] Example 3
[0090] A nanocellulose graphene quantum dot high-sensitivity humidity sensor is prepared, comprising the following steps:
[0091] (1) Prepare a nanocellulose dispersion with a concentration of 13 mg / mL and a graphene quantum dot dispersion with a concentration of 2 mg / mL.
[0092] (2) The nanocellulose dispersion is subjected to efficient ultrasonic dispersion for 15 minutes to obtain a uniform nanocellulose dispersion; at the same time, the concentration of the corresponding graphene quantum dot dispersion is configured.
[0093] (3) The nanocellulose dispersion and the graphene quantum dot dispersion are mixed in a certain proportion, and ultrasonically dispersed at an ultrasonic power of 1200 W for 50 min to obtain a uniformly dispersed nanocellulose-graphene quantum dot mixed dispersion; wherein the graphene quantum dots account for 20 wt.% of the total dry weight of the nanocellulose and the graphene quantum dots.
[0094] (4) Adding a certain amount of polydimethylsiloxane (PDMS) to the mixed dispersion, and obtaining a mixed dispersion of the three after magnetic stirring and ultrasonic dispersion; wherein PDMS accounts for 10 wt.% of the total dry weight of nanocellulose, graphene quantum dots, and PDMS.
[0095] (5) The mixed dispersion of the above three was placed in a vacuum freeze dryer, the temperature was controlled at -50°C, and the sample was frozen for 6 hours. The sample was then taken out and placed on a sample rack, and vacuum dried for 24 hours to obtain a three-dimensional porous material as a porous humidity sensitive membrane (i.e., nanocellulose / graphene quantum dots / polydimethylsiloxane composite humidity sensitive membrane); its thickness was 0.5 mm. The bending picture of the obtained three-dimensional porous material is shown in the figure below. Figure 8 As shown, the natural state picture is as follows Fig. 9 shown.
[0096] (6) A composite film with high conductivity is prepared by mixing nanocellulose dispersion and carbon nanotubes through ultrasonic dispersion, filtration and drying, and used as the electrode of the sensor; its thickness is 0.1 mm; its square resistance is 23Ω / □.
[0097] (7) PDMS is coated on the upper and lower surfaces of the three-dimensional porous material, and a highly conductive composite film cut according to predetermined specifications is pasted on the upper and lower surfaces of the three-dimensional porous material coated with PDMS, and then cured at 85° C. for 6 hours to obtain a capacitive nanocellulose graphene quantum dot high-sensitivity humidity sensor.
[0098] (8) Lay the assembled sensor flat and evenly apply conductive silver glue on the upper and lower sides of the highly conductive composite film to connect it to the wire and ensure good contact with external equipment.
[0099] The humidity and sensor response sensitivity are monitored by measuring the capacitance changes between electrodes attached with nanocellulose / graphene quantum dots / polydimethylsiloxane composite humidity-sensitive film.
[0100] Result: The humidity sensitivity curve is as follows: Figure 6 As shown in the figure, in the test environment of 25℃ and the humidity range of 11~97%RH, when the humidity continues to increase, the capacitance value of the humidity sensor also continues to increase, and the capacitance output value of the sensor shows a certain curve relationship with the humidity. The response sensitivity of the humidity sensor is defined as the ratio of the capacitance change value to the humidity change value. The humidity-sensitive characteristic curve shows that the response sensitivity of the nanocellulose graphene quantum dot humidity sensor is 1340.17pF / %RH.
[0101] The response time curve is as follows: Figure 7 As shown, the nanocellulose graphene quantum dot humidity sensor was tested in 11% RH and 97% RH humidity environments. It reacted slowly in a high humidity environment, but was able to quickly return to a stable state in a low humidity environment within 2s.
[0102] Comparative Example 1
[0103] The difference from Example 3 is that in step (5), the composite membrane obtained by the mixed dispersion liquid using the suction filtration membrane forming method is used as the humidity sensitive membrane, and the remaining steps are consistent with Example 3.
[0104] The scanning electron microscope image of the porous composite humidity sensitive membrane prepared in Example 3 is analyzed. Figure 4 The humidity sensitive film prepared in Example 1 was analyzed by electron microscope, and the results were as follows Figure 5 As shown, from Figure 4 and 5 It can be seen that the porous structure of the porous humidity-sensitive membrane prepared in Example 3 is obvious, while the porous structure of the humidity-sensitive membrane prepared in Comparative Example 1 is not obvious.
[0105] This is because the mixed dispersion can be frozen using vacuum freeze-drying technology, and then the ice crystals can be removed by sublimation under vacuum conditions, which promotes the formation of the pore structure of the composite humidity-sensitive membrane and ultimately obtains a porous composite humidity-sensitive membrane. However, in the humidity-sensitive membrane obtained by suction filtration, the nanocellulose and graphene quantum dots are tightly assembled under the action of suction during the preparation process, which is not conducive to the construction of a porous network structure, and therefore its porosity is poor.
[0106] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and the embodiments. They can be applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily realized.
Claims
1. A nanocellulose graphene quantum dot high-sensitivity humidity sensor, characterized in that: include: A porous composite humidity-sensitive membrane is prepared by mixing nanocellulose, graphene quantum dots and polydimethylsiloxane in a certain proportion, wherein the porous composite humidity-sensitive membrane constitutes a sensing surface; A polydimethylsiloxane layer coated on the side of the porous composite moisture-sensitive membrane; a flexible electrode adhered to the side of the porous composite moisture-sensitive membrane through a polydimethylsiloxane layer; a wire connected to the flexible electrode; The nanocellulose is one or more of nanofibrillar cellulose, cellulose nanocrystals and bacterial cellulose; The graphene quantum dots are one or more of graphene quantum dots and graphene oxide quantum dots; The flexible electrode is a nanocellulose carbon nanotube composite film with a thickness of 0.01-0.1 mm and a square resistance of 20-390Ω / □; Connect the anti-interference shielded wire to the flexible electrode through conductive silver glue; Also includes: A rubber belt, with fasteners at both ends thereof so as to be fastened into a loop or to other devices, a plurality of grooves are arranged along the belt surface of the rubber belt, the grooves may or may not pass through the rubber belt, the shape of the grooves matches the shape of the porous composite humidity-sensitive membrane so that the porous composite humidity-sensitive membrane is embedded in the grooves, and the side walls of the grooves are also provided with recessed grooves so as to accommodate the flexible electrodes, a wire track is arranged on either side of the groove, the wire track extends straightly inside the rubber belt along the length direction of the rubber belt, and the wire passes through the recessed groove into the wire track and is arranged along the wire track; A central processing module, which is buried inside the rubber belt and close to the two ends of the rubber belt, the central processing module includes a processing unit and a storage unit, and the wire extends and is connected to the processing unit; The wiring terminals are arranged at both ends of the rubber belt for connecting with other devices, and the wiring terminals are connected to the central processing module.
2. A green preparation process for the nanocellulose graphene quantum dot high-sensitivity humidity sensor according to claim 1, characterized in that: The following steps are involved: Step 1: After mixing nanocellulose and graphene quantum dots in a certain proportion, ultrasonically disperse the mixture to obtain a dispersion; uniformly mix polydimethylsiloxane with the obtained dispersion to obtain a mixed dispersion; and vacuum freeze-dry the obtained mixed dispersion to prepare a porous composite humidity-sensitive membrane; Step 2: evenly coating polydimethylsiloxane on the left and right sides of the porous composite humidity-sensitive membrane, wherein the upper and lower sides of the porous composite humidity-sensitive membrane form sensing surfaces; Step 3, pasting the nanocellulose carbon nanotube composite film to the left and right sides of the porous composite humidity sensitive film to form a flexible electrode; Step 4: Connect the wire used to connect to the external device to the flexible electrode to obtain the nanocellulose graphene quantum dot high-sensitivity humidity sensor.
3. The green preparation process of the nanocellulose graphene quantum dot high-sensitive humidity sensor according to claim 2, characterized in that: Specifically include: Step A, preparing a nanocellulose dispersion with a concentration of 1-50 mg / ml and a graphene quantum dot dispersion with a concentration of 1-20 mg / ml; Step B, subjecting the nanocellulose dispersion and the graphene quantum dot dispersion to high-efficiency ultrasonic dispersion for 5 to 60 minutes respectively to obtain uniform nanocellulose dispersion and graphene quantum dot dispersion; Step C, mixing a uniform nanocellulose dispersion and a graphene quantum dot dispersion in a certain proportion, and ultrasonically dispersing for 20 to 120 min at an ultrasonic power of 400 to 1200 W to obtain a uniformly dispersed nanocellulose graphene quantum dot dispersion; wherein the graphene quantum dots account for 0.5 to 100 wt.% of the total dry weight of the nanocellulose and the graphene quantum dots; Step D, adding a certain amount of polydimethylsiloxane to the nanocellulose graphene quantum dot dispersion, and obtaining a mixed dispersion after magnetic stirring and ultrasonic dispersion; wherein the polydimethylsiloxane accounts for 10-50 wt.% of the total dry weight of the nanocellulose, graphene quantum dots and polydimethylsiloxane; Step E, placing the obtained mixed dispersion into a vacuum freeze dryer, controlling the temperature to -50 °C, freezing for 2 to 6 hours, then taking it out and placing it on a sample rack, vacuum drying for 24 to 72 hours, to obtain a porous composite humidity-sensitive membrane; the porous composite humidity-sensitive membrane has a thickness of 0.5 to 20 mm; Step F, mixing the nanocellulose dispersion and the carbon nanotubes, and subjecting the mixture to ultrasonic dispersion, suction filtration, and drying to prepare a nanocellulose carbon nanotube composite film; the nanocellulose carbon nanotube composite film has a thickness of 0.01-0.1 mm and a square resistance of 20-390Ω / □; Step G, coating polydimethylsiloxane on the side of the porous composite humidity-sensitive membrane, pasting the nanocellulose carbon nanotube composite membrane cut according to a predetermined specification on the side of the porous composite humidity-sensitive membrane, and then curing at 85° C. for 6 to 12 hours to obtain an assembled sensor; Step H: lay the assembled sensor flat, evenly apply conductive silver glue on both sides of the nanocellulose carbon nanotube composite film, connect it with the wire, and ensure good contact with external equipment.
Citation Information
Patent Citations
Nano-crystalline cellulose graphene quantum dot high-sensitivity humidity sensor
CN213022954U
Cited By
An ultrafast humidity sensor, a preparation method and application thereof
CN122859477A